Group counseling services with a Gestalt approach to coping with quarter life crisis - Lia Mita Syahri (Counseling and Humanities Review, 2021)
As people get older, individuals will think about what their future state will be, each individual has a different view of the future, many individuals are trapped in a state of anxiety, fear and sadness even to the point of being stressed when they have to be faced with the question of how the future will be. , this is known as the quarter life crisis. The purpose of this study is to help individuals overcome the quarter life crisis by using the approach given in groups. This type of research is a literature study by utilizing articles or journals related to group counseling, the gestalt approach and the quarter life crisis. The findings of this study reveal that using the gestalt approach by means of group counseling is effective in helping individuals who are experiencing a quarter life crisis, one of the techniques used is the practice of being responsible.